KOORDINASI PERWAKILAN INDONESIA DAN DIREKTORAT JENDERAL IMIGRASI DALAM MENANGANI WARGA NEGARA INDONESIA YANG DIDEPORTASI: Coordination between Indonesian Representatives and the Directorate General of Immigration in Handling Deported Indonesian Citizens - Muhammad Kevin Kwee; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2026)
The increase in deportation cases indicates weak data integration, procedural differences, and limitations in the protection mechanisms for Indonesian citizens (WNI), which have resulted in delays in the repatriation and handling of deported WNI. Therefore, coordination between representatives of the Republic of Indonesia and the Directorate General of Immigration is needed in handling WNI who are deported from abroad. The research question in this study is: how is the coordination between representatives of the Republic of Indonesia and the Directorate General of Immigration coordinate in handling WNI who are deported from abroad? This study employs a normative legal method, is descriptive in nature, utilizes secondary data obtained through literature studies, analyzes the data qualitatively, and draws conclusions deductively. The results of the research and conclusions show that effective coordination requires data integration, clear communication channels, and standardised procedures, from notification to repatriation. Harmonisation of institutional roles is also important to ensure that the handling of deported Indonesian citizens can be carried out quickly, accurately, and in accordance with the principles of state protection.